(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
The aim of this study was to detect antibiotic residues in table eggs consumed in Khartoum State- Sudan. A total of 157 chicken egg samples were collected from 32 poultry farms and 74 sale points. A structured questionnaire was also used to gather information about the hygienic status of the farms, common signs of diseases, awareness of farmers and type of antibiotics used. It was found that diarrhea was present in 34.6% of the farms and the most frequently used antibiotic was tetracycline in 36.4% of the farms. The farmers were supervising their own farms in 57.6% of the farms, and 94% of the farmers lack the knowledge about withdrawal period. The disc assay method and Premi test kit were used for antibiotic residues detection. The total number of positive reactors was 49.6% and 12.7% respectively. Using the Kappa statistic the agreement between the two tests was 0.30 ( poor agreement) and the percent of the agreement was 61.7% . The data showed the poor hygienic status of poultry farms with the concomitant use of antibiotics for treatment of diseases and the lack of knowledge regarding the use of antibiotics resulted in the high percentage of positive samples. Although antibiotics were excessively used in poultry farms the Premi test detected lower positive percentage of the positive samples while the disc assay correlated well with this excessive use of antibiotics